Olhares sobre a cidade: termos do bem viver, vadiagem e polícia nas ruas de São Paulo (1870-1890) - Diniz, Mônica (2012)
This research reflect how the procedural documents called the propriety of conduct law that compose the Autos Crimes were used by police in São Paulo and permeated the daily life of the city during the end of Empire. It was through this legal structure that São Paulo police expanded their forms of control before the so-called crimes of conduct , especially idleness and vagrancy and persecuted subjects that is best suited the new society rules and moral. The Costumes of Police / Police of morals worked the street of the capital backed up by decrees and law is a time of social changes political, economic and urban. We seek to discuss as occurred the relationship between the subjects considered criminals and the police, the debate, about the people who acted and the police that reacted, the assessments and the resistances. We reflect on these questions by means of selected documentation between processes of breach of the propriety of conduct law, Code of Postures of the city, Reports of Chiefs of Police, police records and memorialists